2016
DOI: 10.1039/c6en00007j
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of metal-based engineered nanomaterials on soil communities

Abstract: A comprehensive review of the effects of metal-based nanoparticles on trophic groups, interactions, ecosystem functions and biodiversity of soil communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
74
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(77 citation statements)
references
References 166 publications
(405 reference statements)
2
74
1
Order By: Relevance
“…As compared to silver nanoparticles, effects of zinc oxide nanoparticles on soil bacteria are less studied [87,88]. Although the present study showed negligible effect of zinc oxide nanoparticles on soil bacteria, other studies have shown that they affect soil bacteria as well as soil enzymes at concentrations ranging from 0.1 to 2000 µg/g of soil [34,36,91,92].…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…As compared to silver nanoparticles, effects of zinc oxide nanoparticles on soil bacteria are less studied [87,88]. Although the present study showed negligible effect of zinc oxide nanoparticles on soil bacteria, other studies have shown that they affect soil bacteria as well as soil enzymes at concentrations ranging from 0.1 to 2000 µg/g of soil [34,36,91,92].…”
Section: Discussioncontrasting
confidence: 61%
“…Both the pure culture study and the soil microcosm study confirm the inhibitory effects of silver nanoparticles on soil bacteria. Perturbations in microbial community structure due to these nanoparticles have also been reported in other soils [86][87][88]. These studies have used a wide range of concentrations of silver nanoparticles from 0.01 µg/g to 1815 µg/g of soil and varying exposure times, of one day to one year [39,72,[82][83][84][85]89].…”
Section: Discussionmentioning
confidence: 85%
“…As primary producers, plants are key for any community to function as they are responsible for converting solar energy into organic matter that can be used by other trophic groups (McKee & Filser 2016). Plants serve as a potential pathway for the transportation of NPs (Rico et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies (e.g., Hänsch and Emmerling, 2010;Feng et al, 2013;Schlich et al, 2013b; have shown that AgNP at environmentally relevant concentrations below 1 mg Ag kg −1 cause adverse effects to soil organisms of various trophic levels (McKee and Filser, 2016). Predicted environmental concentrations of AgNP in soil and sludgeamended soil differ between studies, but all lay in the ng to µg Ag kg −1 soil range.…”
Section: Introductionmentioning
confidence: 99%
“…The focus in ecotoxicological testing of AgNP in soil has, thus far, been more on microorganisms (Schlich et al, 2013b;Engelke et al, 2014;McKee and Filser, 2016), earthworms (Heckmann et al, 2011;Shoults-Wilson et al, 2011a;Schlich et al, 2013a;van der Ploeg et al, 2014;Novo et al, 2015), enchytraeids (Gomes et al, 2013(Gomes et al, , 2015Ribeiro et al, 2015;Bicho et al, 2016) and nematodes (Roh et al, 2009;Meyer et al, 2010). Collembola have received less attention.…”
Section: Introductionmentioning
confidence: 99%